Virtual DOM Implementation in KissJS - M.W.M.R.C.T.B. Madigasekara; S.P.P.P. Wanigarathne; P.D.G.N.T.D. Dharmasinghe; Dr. Nuwan Kodagoda; A.G.S.D. Wickramarathna; Dr. Jeewaka Perera (International Journal of Engineering and Management Research, 2022)
In this fast-paced modern world, time is a major asset for most people, including web developers. When developing web applications, the language or framework being used should help the developer create applications fast and efficiently, but at the same time it should be simple enough for them to grasp it quickly. This proposed framework takes into consideration the pros and cons of modern Single Page Application (SPA) development frameworks and tries to use some their approaches to achieve efficiency, and at the same time use its own ways to simplify other tasks that are complex in the aforementioned frameworks. The main objective this framework will try to accomplish is simplify the state management process. However, this paper will focus on the change detection aspect of the framework. The method of change detection used in the framework is the virtual DOM. Reasons for moving forward with this approach will be discussed later in the paper.